Analisis Faktor-Faktor yang Mempengaruhi Peringkat Sukuk di Indonesia - Siddiqoh, Siddiqoh; Rini, Rini (Universitas Muhammadiyah Jakarta, 2025)
Objectives: This study aims to analyze the factors that affect the ranking of sukuk. This analysis is useful for optimizing sukuk investment decision-making. Design/method/approach: This quantitative research uses data from the annual reports of companies with sukuk and sukuk rating reports. The sample is 90 sukuk companies listed on the Indonesia Stock Exchange and still outstanding during the 2021-2023 period, so 270 data were obtained. The data were analyzed with panel data regression analysis on SPSS software.Results/findings: The results show that the size of the board of commissioners and sukuk type have a positive influence on the sukuk rating, the leverage variable has a negative influence on the sukuk rating. Variables that have no influence on the sukuk rating are the number of audit committees and asset growth.Theoretical contribution: The findings of this research can improve the understanding in the field of financial accounting and become a reference for conducting further research on sukuk rating.Practice/policy contribution: This study offers investors guidance on the key factors influencing sukuk ratings, which serve as a basis for sukuk investment.Limitations: The years observed in this study are limited from 2021 to 2023. In addition, the research object only focuses on the sukuk of companies listed on the Indonesia Stock Exchange